Hubungan pengetahuan dan sikap wanita usia subur terhadap pemberian imunisasi tetanus toxoid - Handayani, nila (Universitas Aufa Royhan, 2021)
ABSTRAC Immunization is giving the body immunity against a disease by inserting something into the body so that the body is resistant to diseases that are endemic or dangerous for someone. The immunization given to women of childbearing age and pregnant women is TT immunization which is useful for preventing tetanus. Tetanus cases are often found in a number of tropical countries and countries that still have low health conditions.The target set by the Indonesian government regarding the program set by Tetanus Toxoid in WUS is 80%, but in reality the target has not been achieved in accordance with the national target that has been achieved. The research method is descriptive relational using the Cross Sectional approach, the sample was taken using a total sample. The number of samples is 43 people. Data analysis using Chi Square test. The results showed knowledge 0.002 (0.002 <0.05) and 0.000 attitude (0.002 <0.05). The conclusion of this research is that there is a relationship between the knowledge and attitudes of women of fertile age towards giving Tetanus Toxoid immunization in Palopat Pijorkoling Village. it is expected that women of childbearing age will increase their understanding of the benefits of tetanus toxoid immunization and for health workers to further enhance promotional efforts related to tetanus toxoid in women of childbearing age.